PENGARUH KUALITAS PRODUK, HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN (PADA UKM MARTABAK MAS IPUNG DI PERUMAHAN PLAMONGAN INDAH SEMARANG - Luthfan Fazari Harsanto; Wahyu Hidayat (Jurnal Ilmu Administrasi Bisnis, 2017)
Nowadays, the growth of SMEs in Indonesia is growing rapidly in the food sector. This is caused by an interesting food SMEs, such as SMEs Martabak. However, there are still consumers who assess the lack of quality products, price, and locations that exist. It causes a low purchase decisions.This study aims to determine the effect of product quality, price and location to purchasing decisions on SMEs Mas Ipung’s Martabak in Housing Plamongan Indah Semarang.This research is a survey research using questionnaire as its instrument. Population and samples used in this study are consumers who make a purchase in SMEs Mas Ipung’s Martabak. 97 respondents choosing by using Incidental Sampling method, which is a sampling technique that is done by chance.This study concludes that product quality, price and location have positive and significant effect on purchasing decision, either partially or simultaneously. Location variables have the greatest influence of other variables. The results are obtained by analyzing the primary data using validity test, reliability test, cross tabulation, correlation coefficient, simple regression analysis, determination coefficient, significance test (t test) two way.Based on this, the researcher suggested that the owner can pay attention to the quality products, price and location layout of SMEs.